HUBUNGAN PENGETAHUAN DAN SIKAP PEDAGANG DENGAN KANDUNGAN FORMALIN PADA IKAN ASIN (Studi di Pasar Tradisional WiIayah Kabupaten Rembang) - Larasati Dwi Nor Aini; Siti Fatimah Pradigdo; M. Zen Rahfiluddin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Dangers of Food Additives have an impact on the human body, for example the body will experience a decline in internal organ function such as causing cancer of the respiratory tract, digestive tract infections, sore throat, dizziness, nausea, vomiting, and can cause several fatal diseases such as leukemia. This is knowing the formaldehyde content found in salted fish and the factors that influence the use of formaldehyde in the Rembang Regency area. This research uses analytic observational research with cross sectional approach. The samples in this study were all the population of 34 salted fish traders in all traditional markets in the Rembang Regency. The instruments in this study used a structured questionnaire and formalin test conducted at the Nutrition Laboratory of the Faculty of Public Health, Diponegoro University. Data processing in this research uses a statistical test that is Chi-Square test. The results of this study are from 34 respondents obtained by respondents with good knowledge as much as 58.8% and respondent attitudes classified as good as much as 82.4%. Laboratory test results showed that samples containing formaldehyde amounted to 85.3% and those that did not contain formaldehyde amounted to 14.7%. Samples that did not contain formalin layur fish type. Based on the Chi-square statistical test, p = 1.00 was obtained in the relationship between traders 'knowledge and formalin content in salted fish and p = 0.559 in the relationship between traders' attitudes and formalin content in salted fish. Based on the results of statistical tests that there is no relationship between the knowledge of traders and the attitude of traders to the formaldehyde content of salted fish. This can be used as an improvement by several related parties, namely, the Health Office who can conduct further review of formalin in salted fish in the traditional markets in the Rembang Regency